Study guides

☆☆

Q: 3t - 8

Write your answer...

Submit

Still have questions?

Related questions

t+8 = 2-3t add 3t to both sides: 4t+8 = 2 take 8 away from both sides: 4t = -6 divide both sides by 4: t = -6/4 = -3/2

In 2t+8 19

3t - 15 = -9 3t - 15 (+15) = -9 (+15) 3t = 6 3t (/3) = 6 (/3) t = 2

3t+11 = 29 3t = 29-11 3t = 18 t = 6

t is equal to 6

3t - 1

3t in lb.

5-3t = 0.77 -3t = 0.77-5 -3t = -4.23 t = 1.41

t - 2t - 3t = 32t - 5t = 32-4t = 32t = -8According to the information given in the question, t can't equal 8.

3,000 is greater then 3t

S = 3 st + 3t = 6 st = 6 - 3t s = (6 - 3t)/t = 6/t - 3

It is an equation. Taking it step by step: 17 = 3t - 4 17 + 4 = 3t 21 = 3t 7 = t So the value of t is 7.

2t - 8 = 3t + 12 First you remove the outer numbers from one side of the equation. In this case, 12. But whatever you do to one side, you have to do the same for the other side. 2t - 8 - 12 = 3t Then put all the terms with unknowns on one side. -8 - 12 = 3t - 2t We can simplify this into... -20 = t so... t = -20. hope that helps. :)

4

2t x 3t = 6t2

3t + 9 = 3(t + 3)

3 t squared (3t^2)

4+3t = 22 3t = 22-4 t = (22-4)/3 t = 6

if you mean T-3t+2t+4 (T and t is different variables):T-3t+2t+4=T-t+4if you mean t-3t+2t+4:t-3t+2t+4=4

Songs written by 3T are administered by EMI.

6 < 3t

Plus 3T

3t + 7 = 2t - 5 3t = 2t - 12 t = -12

8

It is (3t-2)(3t+2) when factored and it is the difference of two squares

People also asked